Interface high-temperature superconductivity. (10th October 2016) - Wang, Lili; Ma, Xucun; Xue, Qi-Kun
Abstract: Cuprate high-temperature superconductors consist of two quasi-two-dimensional (2D) substructures: CuO2 superconducting layers and charge reservoir layers. The superconductivity is realized by charge transfer from the charge reservoir layers into the superconducting layers without chemical dopants and defects being introduced into the latter, similar to modulation-doping in the semiconductor superlattices of AlGaAs/GaAs. Inspired by this scheme, we have been searching for high-temperature superconductivity in ultra-thin films of superconductors epitaxially grown on semiconductor/oxide substrates since 2008. We have observed interface-enhanced superconductivity in both conventional and unconventional superconducting films, including single atomic layer films of Pb and In on Si substrates and single unit cell (UC) films of FeSe on SrTiO3 (STO) substrates. The discovery of high-temperature superconductivity with a superconducting gap of ∼20 meV in 1UC-FeSe/STO has stimulated tremendous interest in the superconductivity community, for it opens a new avenue for both raising superconducting transition temperature and understanding the pairing mechanism of unconventional high-temperature superconductivity. Here, we review mainly the experimental progress on interface-enhanced superconductivity in the three systems mentioned above with emphasis on 1UC-FeSe/STO, studied by scanning tunneling microscopy/spectroscopy, angle-resolved photoemission spectroscopy and transport experiments. We discuss the roles of interfaces and a possible pairing mechanism inferred from these studies.